Varying Interaction Patterns to Create Communicative Teaching and Learning - Rambe, Sokhira Linda Vinde (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
This article has purposes to determine types and variations of interaction patterns that the lecturers applied in teaching. It is also to describe advantages of the interactions in students’ learning process. A qualitative research was implemented where 10 lecturers who teach English at Language Development Center of IAIN Padangsidimpuan involved in the study. To collect the data, interview were given to lecturers and observation was done in ten classrooms. Then, descriptive data analysis was implemented in analyzing the data that were collected. The study revealed that all lecturers had tried hard to vary the interaction patterns in teaching. Several interaction patterns were seen dominantly used by lecturers, i.e. group work, full-class interaction, close and open-ended questioning, choral responses, and individual work. Moreover, there are some advantages that students can take from the variations of interaction patterns, namely; (1) students can share ideas with friends and lead them to be active, (2) students have lots of chances to practice English skills, (3) and interaction patterns makes the learning interesting and fun.